Antimicrobial Resistance of Escherichia coli Causing Uncomplicated Urinary Tract Infections: A European Update for 2014 and Comparison with 2000 and 2008. Issue 4 (December 2015) - Kahlmeter, Gunnar; Åhman, Jenny; Matuschek, Erika
Abstract Introduction The objective of this study was to provide an update on the resistance ofEscherichia coli in women with acute uncomplicated urinary tract infections (UTIs) in France, Germany, Spain, Sweden, and the United Kingdom (UK) to mecillinam [amdinocillin (United States Adopted Name)], amoxicillin–clavulanic acid, cefadroxil, nitrofurantoin, ciprofloxacin, and trimethoprim, and to compare the results with resistance in the ECO.SENS I and II surveys in 2000 and 2008, respectively. Methods The susceptibility ofE. coli in France (166 isolates), Germany (133 isolates), Spain (169 isolates), Sweden (137 isolates), and the UK (124 isolates) was determined by disc diffusion according to European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints and methodology. Resistance rates were compared using Fisher's exact test, 2-tailed, withP  < 0.05 indicating statistical significance. Results Since 2000, there has been a significant increase in resistance to cefadroxil in Germany (1% to 12%) and Spain (3% to 8%), to ciprofloxacin in Germany (2% to 21%), Spain (15% to 31%), Sweden (0% to 7%), and the UK (1% to 15%), to trimethoprim in Germany (23% to 37%), Spain (25% to 37%), Sweden (9% to 17%), and the UK (13% to 46%), to mecillinam in Spain (1% to 6.5%), and to nitrofurantoin in the UK (0% to 6%); there was also a significant decrease in resistance to nitrofurantoin in Spain (4% to 0%). Since 2008, there has been a significant increase in resistance to ciprofloxacin in Sweden (3% to 15%) and the UK (1% to 15%), and to trimethoprim (13% to 46%) and nitrofurantoin (0% to 6%) in the UK. Conclusion E. coli isolates from women with acute uncomplicated UTIs have increasing antimicrobial resistance, particularly to ciprofloxacin and trimethoprim. However, resistance to mecillinam and nitrofurantoin mostly remains low. Funding LEO Pharma.